Analysis of Competencies of Sales Personnel of Banking Sector in Pakistan - Imran, Faisal (My University, 2015)
The banking sector of Pakistan is playing a pivotal role in the economy of country. Over the last two decades, private banks have progressed rapidly. It resulted into highly competitive environment in this sector which raised the need of highly competitive human resources, especially sales personnel who plays a very important role in the development of banks. The purpose of this research work is to analyse the existing competencies of these sales personnel and to propose a framework for the improvement in the key sales competencies of these personnel to enhance their effectiveness in the banking sector of Pakistan. The first research question investigates the creative tension of these personnel for sales competencies. Second research question is related to determining the appropriate training and development methods to improve these competencies. While the aim of last research question is to determine the appropriate activities which can help in enhancing the current competencies of sales personnel. A self-evaluation tool Astroid 1.0 is used for data collection, which consists of 120 pre-formulated questions. A sample group of 20 sales personnel from UBL Pakistan participated in this study. This tool determines the current and target state of competencies and describes the creative tension for each competency in different graphical forms. This study resulted into practical framework to enhance the competencies of sales personnel. It makes valuable contribution into applying HRM practices which will lead banking sector to develop the competencies of their sales personnel.
Keywords: Competencies; Sales Personnel; Banking Sector of Pakistan; Evolute; Astroid; Training and Development; HRM; Creative Tension.; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in International Business|; fi=Digitaalinen media|en=Digital media|